IT outsourcing success in the public sector: Lessons from e-government practices in Korea. (March 2016) - Moon, Junghoon; Choe, Young Chan; Chung, Miri; Jung, Gu Hyun; Swar, Bobby
Recent studies on IT (Information Technology) outsourcing reveal the growing trend and widely accepted management practice of IT outsourcing in the public sector. To achieve more from this practice it is essential to identify and examine the success factors. In this regard, this study conducts an empirical investigation on IT outsourcing projects for e-government. A framework is proposed and 13 IT outsourcing success factors from the private sector are identified through a literature review. The framework demonstrates the impact of four categories, organizational environment, contract/project characteristics, project management, and partnership management on IT outsourcing. A survey of IT managers responsible for managing IT outsourcing projects in Korean government organizations was conducted and 178 IT outsourcing projects for e-government initiated by 56 different government organizations were analyzed. The findings are then compared with general beliefs on IT outsourcing in the private sector. Findings and lessons from the empirical investigation of this study provide useful guidelines for IT managers in the public sector.